2017
DOI: 10.1080/14737167.2017.1281744
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare burden of depression in adults with arthritis

Abstract: Introduction Arthritis and depression are two of the top disabling conditions. When arthritis and depression exist in the same individual, they can interact with each other negatively and pose a significant healthcare burden on the patients, their families, payers, healthcare systems, and society as a whole. Areas covered The primary objective of this review is to summarize, identify knowledge gaps and discuss the challenges in estimating the healthcare burden of depression among individuals with arthritis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 175 publications
(169 reference statements)
2
30
0
Order By: Relevance
“…Similar to previous studies of adults with arthritis overall and for arthritis subtypes (e.g., osteoarthritis or rheumatoid arthritis) ( 2 , 4 , 5 ), the prevalence of anxiety symptoms exceeded that of symptoms of depression. Despite this, adults with anxiety symptoms less commonly reported taking medications for their symptoms than did those with symptoms of depression; the prevalences among those with either anxiety or depression symptoms were not statistically different for speaking with a mental health professional.…”
Section: Discussionsupporting
confidence: 83%
“…Similar to previous studies of adults with arthritis overall and for arthritis subtypes (e.g., osteoarthritis or rheumatoid arthritis) ( 2 , 4 , 5 ), the prevalence of anxiety symptoms exceeded that of symptoms of depression. Despite this, adults with anxiety symptoms less commonly reported taking medications for their symptoms than did those with symptoms of depression; the prevalences among those with either anxiety or depression symptoms were not statistically different for speaking with a mental health professional.…”
Section: Discussionsupporting
confidence: 83%
“…Lehnert et al( 2011) and Molosankwe et al (2012) found that coexistent depression increased costs of treating diabetes. Sambamoorthi et al (2017) found an increase in costs of treating arthritis when depression coexisted. Baumeister et al (2012) found higher direct, but not indirect costs in the treatment of chronic back pain with comorbid depression.…”
Section: Discussionmentioning
confidence: 99%
“…Such pain and disabilities associated with RA may contribute to a higher prevalence of depression in individuals with RA compared to healthy controls [ 3 ]. An expert review of depression in arthritis reported that the prevalence of depression in adults with RA can be as high as 66.2% [ 4 ]. A systematic review and meta-analysis of 72 studies estimated the prevalence rate to be 16.8% [ 5 ].…”
Section: Introductionmentioning
confidence: 99%